Academic Tutoring in Virtual Education: A Case Study in University Students - Núñez-Hernández, Corina (2023)
Tutoring plays a crucial role in students' success by providing them with academic support, helping them overcome obstacles, and fostering their confidence in professional development. Specifically, in higher education, tutoring aims to complement academic training and address dropout and educational lag. Virtual tutoring offers advantages in terms of scope and logistics, but also presents challenges in building online relationships. The interaction between teachers and students is a key factor that influences the motivation of the latter, and personalized virtual tutoring is highly valued by distance students. This study employed a descriptive and quantitative methodology, collecting data from a representative sample of higher education students in Ecuador. An adapted questionnaire was used to assess students' satisfaction with the university tutor, as well as the organization and content of the tutoring sessions. The results revealed satisfactory levels regarding the tutor's personal skills, the work performed, and university tutoring in general, both in face-to-face and virtual modalities. The conclusions highlight the importance of virtual academic tutoring for student success, emphasizing its personalized support and positive impact on motivation. Further research is recommended to delve into the factors influencing satisfaction with academic tutoring and to utilize these findings to improve the tutoring process in higher education.